Performance in vertical jump and use of elastic energy in badminton players - Lima, Karen Christie Gomes (2019)
Introduction: Badminton has a large predominance of jumps representing an important part of the sporting gestures and repeated short movements with changes of direction in high intensity. Vertical jumps, countermovement (CMJ) and squat jump (SJ) are widely used to estimate the power of lower limbs and the difference between these jumps signifies a storage and use of potential elastic energy (EPE). Objective: The research seeks to verify vertical jump performance and EPE utilization in badminton players. Materials and Methods: Anthropometric measures (weight and height) and then vertical jumps: SJ and CMJ were performed on 12 Brazilian badminton players (7 men and 5 women). Results: The characteristics of these players were respectively: mean age of 15.58 ± 2.39 years, body mass 58.21 ± 11.99 and height 166.67 ± 10.63. There was a difference in performance between men (29.38 ± 6.42) and women (16.96 ± 4.65) in the crouching jump, as well as in the countermovement (men 27.06 ± 5.94 and Women 17, 77 ± 5.22). As for the elastic index, women obtained 4.49% ± 0.05 and men 7.17% ± 4.07. Discussion: The IE found in this study is considered low according to the literature, and there is a need for training that improves this variable. However, they may not reflect a low level of performance of these athletes, due to the divergences of values found and sports modality of the evaluated ones. Conclusion The power of lower limbs and IE found in these players were not satisfactory according to the literature. Due to its importance it is essential the training adequacy to improve this variable.